Arthropods of Canadian Grasslands (Volume 1): Ecology and Interactions in Grassland Habitats 2010
DOI: 10.3752/9780968932148.ch12
|View full text |Cite
|
Sign up to set email alerts
|

Galls induced by cynipid wasps of the genus Diplolepis (Hymenoptera: Cynipidae) on the roses of Canada's grasslands

Abstract: Abstract. Thirteen species of cynipid wasps of the genus Diplolepis induce structurally distinct galls on the three species of wild roses found on the grasslands of western Canada. Three species of Diplolepis gall the short rose, Rosa arkansana, in the Mixed Grassland and Moist Mixed Grassland ecoregions of southern Alberta and Saskatchewan, and eight species gall the common prairie rose, R. woodsii, throughout the prairie grasslands. Five species of Diplolepis gall the larger rose, R. acicularis, in more shad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 51 publications
(80 reference statements)
2
49
0
Order By: Relevance
“…The emergence period of adults is synchronized with that of their host, which occurs soon after the immature galls appear such that the ovipositing females ( Fig. 1) can reach the chambers of developing galls in this narrow window of opportunity (Shorthouse 2010). Eurytomid eggs are brown to black, and with an elongated egg body, and a curved peduncle which may be used to attach the egg to the inside surface of the developing gall chambers or the body of its host ( Fig.…”
Section: Biology Of Eurytomids Associated With Galls Induced By Diplomentioning
confidence: 99%
See 4 more Smart Citations
“…The emergence period of adults is synchronized with that of their host, which occurs soon after the immature galls appear such that the ovipositing females ( Fig. 1) can reach the chambers of developing galls in this narrow window of opportunity (Shorthouse 2010). Eurytomid eggs are brown to black, and with an elongated egg body, and a curved peduncle which may be used to attach the egg to the inside surface of the developing gall chambers or the body of its host ( Fig.…”
Section: Biology Of Eurytomids Associated With Galls Induced By Diplomentioning
confidence: 99%
“…Members of the family Eurytomidae (Hymenoptera: Chalcidoidea) are one of the most common parasitoids associated with cynipid galls on roses in Canada, often comprising up to 40% of the component community (Shorthouse 2010). Bugbee (1951a, b) reported 12 species of Eurytoma Illiger and one species of Tenuipetiolus Bugbee known from galls of Diplolepis, and suggested that most species are monophagous.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations